Analysis of Proportional Fair Scheduling Algorithm for Long Term Evolution (LTE) Uplink - Purnomowati, Endah Budi; Rahma, Muthia; Yuwono, Rudy (International Journal of Control and Automation, 2018)
Scheduling is a radio resource allocation schemes for serving users by an algorithm. The amount of resource blocks that will be allocated is 50 by the 10 MHz bandwidth. The simulation scenario defined as a single cell network with several users in which located among 1-4 km. Proportional Fair algorithm will assigns more resource block to a user who has the highest rate than the average rate. This simulation result shows that SNR value implicates the data rate and modulation scheme applied. The increasing of user distance from eNodeB, will decrease SNR and data rate. Thus, the number of resource block allocated will be decreased. While as the increasing of user number, the value of system’s BER are tend to constant, maximum normalized throughput are increase, and the level of fairness will tend to constant close to ideal value of 1.